HUBUNGAN PERSEPSI LINGKUNGAN TEMPAT TINGGAL DAN PEMANFAATAN SMARTPHONE DENGAN PERILAKU BERPACARAN YANG BERISIKO PADA REMAJA YANG TINGGAL DI DAERAH LOKALISASI GAMBILANGU KOTA SEMARANG - Rahmadani, Ike; Dharminto, Dharminto; Agusyahbana, Farid; Dharmawan, Yudhy (Fakultas Kesehatan Masyarakat, 2018)
Gambilangu (known as GBL) is one of the famous localization complexes found in Semarang and Kendal.Teens who live in the area of localization is very permissive to sex outside of marriage.The purpose of this study was to analyze the association of perception of the recidential environment and and the usage of smartphoneswith the risky dating behavior in teens who live in the lokalisasi GambilanguSemarang city.This study uses descriptive analytic research using cross sectionalstudy.The population is 66 teens in age group 15-19 years who were in RW 5 and 6 Mangkang Kulon village Semarang.Samples were taken from all population numbers that fulfilled inclusion criteria of 40 adolescents.The characteristics of respondents were more than half of the respondents (52,5%), with the larger age group (32,5%), and the highest school or student (75,0%), parents of respondents as private (70,0%) greater than other jobs.Spearman rank correlation test showed statistically pvalue= 0,017 means that there is a significant association between the usage of a smartphone with the risky dating behavior, and pvalue= 0,545, pvalue= 0,658, pvalue= 0,412 it showed that there is no significant association between perception of the recidential environment, reproductive health knowledge and attitudeswith risky dating behavior.Multiple logistic regression statistical test showed pvalue= 0,941 andpvalue= 0,075 it showed that there is significant influence between the usage of smartphones with risky dating behavior.Suggestions for Mangkang Kulon village community that parents supervise and monitor the activities of teenagers for avoiding the use of smartphones to access pornographic sites.